Targeting Transforming Growth Factor-Beta1 (TGF-β1) Inhibits Tumorigenesis of Anaplastic Thyroid Carcinoma Cells Through ERK1/2-NF-κB-PUMA Signaling - Yin, Qiang (Med Sci Monit, 2016)
BACKGROUND: The transforming growth factor-beta (TGF-β) signaling pathway plays a critical role in promoting tumor growth. TGF-β1was found to be overexpressed in anaplastic thyroid cancer (ATC). We therefore tested our hypothesis that targeting TGF-β1 inhibits tumorigenesis of ATC cells. MATERIAL/METHODS: Effects of TGF-β1 stimulation or TGF-β1 inhibition by small interfering RNA (TGF-β1siRNA) on proliferation, colony formation, and apoptosis in 8505C cells in vitro was detected using siRNAs and inhibitors to examine the TGF-β1 signaling pathway. A subcutaneously implanted tumor model of 8505C cells in nude mice was used to assess the effects of TGF-β1 inhibition on tumorigenesis development. RESULTS: TGF-β1siRNAs decreased proliferation and colony formation, and increased apoptosis in 8505C cells in vitro and inhibited tumor growth in vivo. TGF-β1siRNA inhibited phosphorylation ERK1/2 (pERK1/2) and increased p65-dependant PUMA mRNA and protein expression. Knockdown of p65 or PUMA by siRNA reduced TGF-β1siRNA-induced apoptosis, as well as caspase-3 and PARP activation. Upregulation of p65 or PUMA expression by TGF-β1siRNA requires pERK1/2 inhibition. TGF-β1 shRNA inhibited tumor growth in vivo. CONCLUSIONS: Therapies targeting the TGF-β1 pathway may be more effective to prevent primary tumor formation. The ability of this therapy to decrease tumorigenesis may be related to ERK1/2/NF-κB/PUMA signaling.